PENGARUH PRINSIP AL- MUZARA’AH DAN AL- MUKHABARAH TERHADAP PERJANJIAN BAGI HASIL PERTANIAN (STUDI DI KECAMATAN SEMADAM KABUPATEN ACEH TENGGARA) - M. FURQAN (PREMISE LAW JURNAL, 2016)
DOESN PEMBIMBING:1. M. Hasballah Thaib 2. Muhd Yamin 3. Utary Maharany Al-Muzara’ah is tilling someone’s land, such as wet-rice fields and land with the compensation of part of production (half, one third or three fourths) in which the land owner is responsible for the tilling costs and seeds. Meanwhile, Al-Mukhabarah is tilling someone’s land, such as wet-rice fields and land with the compensation of part of production (half, one third or three fourths) in which the person who tills the land is responsible for the tilling costs and seeds. It is very interesting to analyze how the principles of Al-Muzara’ah which at the beginning existed in the community in Semadan Subdistrict, but in the last few years they have changed and used the systems of Al-Mukhabarah in the contracts on production sharing of agricultural lands. The problems of the research were as follows: how about the accomplishment of the principles of Al-Muzara’ah and Al-Mukhabarah towards the contract on production sharing of agricultural land in Semadan Subdistrict, Aceh Tenggara District, what factors prevented the accomplishment of the principles of Al-Muzara’ah and Al-Mukhabarahare in the contract on production sharing of agricultural land, and how about the solution for conflicts in contract which were based on the principles of Al-Muzara’ah and Al-Mukhabarah. Keywords : Al-Muzara’ah, Al-Mukhabarah, Contract on Agricultural Production Sharing